2022
DOI: 10.1096/fasebj.2022.36.s1.r6275
|View full text |Cite
|
Sign up to set email alerts
|

Hyperacetylation of Toll‐like receptor 4 (TLR4): a potential factor contributing to non‐alcoholic liver disease (NAFLD), a silent killer in obesity

Abstract: Background Obesity frequently leads to non‐alcoholic fatty liver disease (NAFLD), the most common liver problem affecting the American population. In fact, the prevalence of NAFLD in adult Americans ranges from 25‐46%. To date, there is no specific treatment for NAFLD. In severe cases, NAFLD can lead to fibrosis and cirrhosis which evolves into nonalcoholic steatohepatitis (NASH). Most patients with NAFLD experience no symptoms, making it a silent killer. Evidence has suggested that Toll‐like receptor 4 (TLR4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Toll-like receptor 4 (TLR4) is an important member of the TLR family. Studies have shown that TLR4 is a key pattern recognition receptor for LPSs and plays an important role in the connection between the innate immune system and metabolic syndrome ( Csak et al., 2011 ; Maddie et al., 2022 ; Sharifnia et al., 2015 ). During the progression of MAFLD, serum LPS levels and hepatic TLR4 expression were elevated in patients, while the gut microbiota diversity and biological colonization resistance of gut microorganisms were decreased ( Thuy et al., 2008 ; Dapito et al., 2012 ).…”
Section: A Potential Mechanism For the Treatment Of Mafld By Targetin...mentioning
confidence: 99%
“…Toll-like receptor 4 (TLR4) is an important member of the TLR family. Studies have shown that TLR4 is a key pattern recognition receptor for LPSs and plays an important role in the connection between the innate immune system and metabolic syndrome ( Csak et al., 2011 ; Maddie et al., 2022 ; Sharifnia et al., 2015 ). During the progression of MAFLD, serum LPS levels and hepatic TLR4 expression were elevated in patients, while the gut microbiota diversity and biological colonization resistance of gut microorganisms were decreased ( Thuy et al., 2008 ; Dapito et al., 2012 ).…”
Section: A Potential Mechanism For the Treatment Of Mafld By Targetin...mentioning
confidence: 99%